2014
DOI: 10.5539/ies.v7n11p28
|View full text |Cite
|
Sign up to set email alerts
|

School Effects, Gender and Socioeconomic Differences in Reading Performance: A Multilevel Analysis

Abstract: The purpose of this paper is to examine the characteristics of Albanian secondary schools, which are associated with reading achievement and the effects of gender and socio-economic status on reading performance of 15-year-old students. This study used data on the background and achievement of 4,596 students in 181 Albanian schools from the 2009 Programme for International Student Assessment (PISA). Given the nested structure of the data, two-level Hierarchical Linear Modeling (HLM) methods were used to addres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
4
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 41 publications
4
4
0
2
Order By: Relevance
“…8, No. 2; This is in line with previous research of learning environments and satisfaction (Ibrahim et al, 2014;Majeed, Fraser, & Aldridge, 2002).The results of this study are also generally in line with previous findings that students with goals are more (internally) motivated, and usually outperform those without them (Maehr & Midgley, 1991;Perry & Van de Kamp, 2000;Shera, 2014). The results of this study are also in congruence with authors that stress adults' need for transparent demands, well-structured classes and strong teacher or peer support (Wlodkowski, 2008).…”
Section: Discussionsupporting
confidence: 83%
“…8, No. 2; This is in line with previous research of learning environments and satisfaction (Ibrahim et al, 2014;Majeed, Fraser, & Aldridge, 2002).The results of this study are also generally in line with previous findings that students with goals are more (internally) motivated, and usually outperform those without them (Maehr & Midgley, 1991;Perry & Van de Kamp, 2000;Shera, 2014). The results of this study are also in congruence with authors that stress adults' need for transparent demands, well-structured classes and strong teacher or peer support (Wlodkowski, 2008).…”
Section: Discussionsupporting
confidence: 83%
“…Araştırma kapsamında ele alınan değişkenler okul ve öğrenci düzeyi olmak üzere 2 düzeyde ele alınmaktadır (Lee, 2000). Öğrenci ve okul düzeyinde ele alınan değişkenler yardımıyla öğrencilerin matematik okuryazarlık düzeyleri yordanmaya çalışıldığından sonuç değişkeni olarak PVMATH şeklinde kodlanan matematik puanlarının ortalaması kullanılmıştır (Shera, 2014). Verilerin okul ve öğrenci düzeyinde hiyerarşik bir yapıya sahip olması sebebiyle analizler HLM 7 programıyla gerçekleştirilmiştir.…”
Section: Verilerin Analiziunclassified
“…PISA 2009 Arnavutluk verilerinin iki aşamalı regresyon analizi ile test edildiği çalışmada okullar arasındaki farklılık toplam varyansın %22'lik bir kısmını açıklamaktadır (Shera, 2014). Elde edilen bu sonuç çalışmanın bulguları ile benzerlik gösterse de Türkiye örnekleminde okullar arasındaki farklılığın PISA matematik başarısındaki toplam varyansı açıklama oranı %63 gibi oldukça büyük bir değerdir.…”
Section: Tartışma Sonuç Ve öNerilerunclassified
“…Much evidence has demonstrated that parental background such as socioeconomic status (SES) and educational level is significantly associated with children's reading achievement in both Western and Chinese cultural contexts (e.g., Aikens & Barbarin, ; Chiu & McBride‐Chang, ; Kieffer, ; Shera, ). As to the relationship between family SES and early reading ability, the general agreement is that children from higher SES families will have better early reading ability (e.g., Aikens & Barbarin, ; Snow, Burns, & Griffin, ).…”
Section: Introductionmentioning
confidence: 99%